Simulating latrine conditions to assess perfume performance against malodour. (16th April 2018) - Chappuis, Charles Jean‐François; Huber, Robin; Niclass, Yvan; Starkenmann, Christian
Abstract: To evaluate perfume performance in toilets, we built model toilets in which critical factors such as background malodour, climate, and airflow were controlled. The models were equipped with an odour generator that injected hydrogen sulfide, methyl mercaptan, butyric acid, para‐cresol, and indole, allowing us to accurately and reliably reconstitute toilet malodour headspace. The malodorant concentrations matched the quantitative headspace analysis performed in African and Indian toilets. The toilet malodour headspace performance was validated by chemical and sensory analysis. Olfactory stimuli were presented to participants in different simulated climates to assess the effect of climate on the perception of odours. The sensory data show that increasing temperature and humidity decreased the intensity ratings of odours without altering their quality. Perfume can be delivered in these toilets by forced evaporation to control the headspace concentration, or by delivery systems such as cellulosic pads, liquids, and powders. Our experimental set‐up allowed us to establish dose–response curves to assess the performance of a perfume in reducing toilet malodour and increasing perceived pleasantness. Abstract : To evaluate perfume performance in toilets, we built model toilets in which critical factors such as background malodor, climate, and airflow were controlled. The models were equipped with an odor generator allowing us to accurately and reliably reconstitute toilet malodor headspace. The toilet malodor headspace performance was validated by chemical and sensory analysis. Olfactory stimuli were presented to participants in different simulated climates to assess the effect of climate on the perception of odors.